(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
Writing is an important skill for language production. However, it is considered as one of the most significant problems that affect not only native English speakers, but also hundreds of students that are learning English as a second or foreign language around the world. Thus, students face many challenges in writing. The fact that students do not have interest in the Composition writing leads them to be poor writers, increase the errors in their homework, write run-on sentences and incoherent paragraphs. Therefore, the present study aims to investigate problems in undergraduate ESP learners’ writing and factors that hinder their writing skills. It also aimed at obtaining suggestions on how to improve learners’ writing skills. For this purpose, teachers must improve their students writing skills by using effective teaching methods and more reading and writing practice.